TO THE ANALYSIS OF DOMESTIC AND FOREIGN EXPERIENCE OF INVESTIGATION IN CUSTOMER LOYALTY - T. Panova (Вестник университета)
The advantages to a company after creating customer loyalty are presented. Analysis of the international and domestic experience in the issue of customer loyalty is presented. The evolution of the concept of customer loyalty considered. The emotional and rational aspects of customer loyalty are discovered. The advantages and disadvantages of approaches to customer loyalty are identified.